Effects of Velogenic Newcastle Disease Virus Strain AFF2240 on the Oncogenes and Marphological Changes of 4T1 Breast Cancer Cell in Balb/c Mice - Eshak, Zolkapli (2011)
The need in finding alternative treatments in breast cancer has become increasingly important as conventional treatment of breast cancer usually have severe side effects. The usage of viruses as an anti-cancer agent has been discovered and studied for decades. The present study was conducted to find a new anti-cancer agent for the treatment of breast cancer. The AF-2240 strain of NDV was propagated in the allantoic fluid of 11-days-old embryonated eggs for 72 hours. The virus was harvested, purified and stored at -800C. The haemagglutination (HA) test conducted on the purified virus showed that the virus obtained was 64 HA unit. The induction of breast cancer was done on the axillary region of female inbred BALB/c mice by using 1 X 104 4T1 breast cancer cells. The mice were then grouped into two big groups; tumour induced and normal control. Out of 10 groups induced with cancer, the cancer only developed in 4 groups and therefore, mice were regrouped into two; tumor -bearing group which consist of groups named cancer treated (CT), cancer control (CC), cancer treated with 0.5 ug/ml of tamoxifen and 32 HA of NDV (CTND32) and cancer control treated with 0.5ug/ml of tamoxifen and 64 HA of NDV (CTND64); and tumor- free groups which consist of groups named normal control (NC), normal treated with 8 HA of NDV (NND8), Normal treated with 16 HA of NDV (NND16), normal treated with 32 HA of NDV (NND32), normal treated with 64 HA of NDV (NND64), cancer treated with 8 HA of NDV (CND8), cancer treated with 16 HA of NDV (CND16), cancer treated with 32 HA of NDV (CND32), cancer treated with 64 HA of NDV (CND64), cancer treated with 0.5 ug/ml of tamoxifen and 8 HA of NDV (CTND8) and cancer treated with 0.5 ug/ml of tamoxifen and 16 HA of NDV (CTND16). Preliminary results showed that NDV-AF2240 alone or in combination with tamoxifen not exceeding 16 HA unit of NDV have an anti-cancer effect. The 4T1 breast cancer models were further evaluated by mean weight of the mice, tumor mass and volume, transmission electron microscopy for localization of the virus, apoptotic peroxidase staining and comet assay for detection of apoptotic cells and RT-PCR for c-myc, c-erbB2 and c-fos oncogenes expression. The mean tumor mass and volume proved that there was no evidence of tumor regression instead; the pattern showed exponential growth of the tumor along with time. The treatment given and the condition of the animals have no effect in term of body weight as there were no significant difference being noticed between tumor-bearing mice and tumor-free mice (p>0.05). It is believed that tumour weight have contributed indirectly to the overall bodyweight in the tumor bearing group. The effectiveness of the treatments was later translated by observing the number of apoptotic cells. All tumors samples exhibited apoptotic features analyzed by using apoptotic peroxidase staining and comet assay. The analysis showed that combination treatments using NDV and amoxifen have no significant effect toward the breast cancer cells. Only CT group which were treated with tamoxifen showed significant (p<0.05) higher number of apoptotic cells compared to the rest of the groups. Like any other types of paramyxovirus, NDV-AF2240 was found to be localized in the cytoplasm of the breast cancer cells observed by using transmission electron microscope. Further analysis of the c-myc, c-erbB2 and c-fos oncogenes revealed that the presences of the oncogenes in all tumor bearing mice group regardless of treatment given. In conclusion, NDV-AF2240 has the potential as an anti-cancer agent if it is used alone or at low HA titre if in combination with tamoxifen. The use of the virus at high HA titre and in combination with tamoxifen has to be monitored with cautioun as it has an antagonist effect.